2020
DOI: 10.1371/journal.pone.0243076
|View full text |Cite
|
Sign up to set email alerts
|

The human axial length and choroidal thickness responses to continuous and alternating episodes of myopic and hyperopic blur

Abstract: Purpose To investigate the change in axial length (AxL) and choroidal thickness (ChT) in response to continuous and alternating episodes of monocular myopic and hyperopic defocus. Methods The right eye of sixteen young adults was exposed to 60 minute episodes of either continuous or alternating myopic and hyperopic defocus (+3 DS & -3 DS) over six separate days, with the left eye optimally corrected for distance. During alternating defocus conditions, the eye was exposed to either 30 or 15 minute cycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 70 publications
3
21
0
Order By: Relevance
“…Exposure to 60 min of continuous hyperopic defocus resulted in a small, but statistically significant axial elongation and subfoveal choroidal thinning. These findings are consistent with previous studies in humans [12][13][14][15][16][17] and other animals. [9][10][11] However, when 1 h of hyperopic defocus was interrupted periodically with 2-min episodes of clear vision, the magnitude of change in axial length and subfoveal choroidal thickness reduced significantly relative to the uninterrupted hyperopic defocus condition.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Exposure to 60 min of continuous hyperopic defocus resulted in a small, but statistically significant axial elongation and subfoveal choroidal thinning. These findings are consistent with previous studies in humans [12][13][14][15][16][17] and other animals. [9][10][11] However, when 1 h of hyperopic defocus was interrupted periodically with 2-min episodes of clear vision, the magnitude of change in axial length and subfoveal choroidal thickness reduced significantly relative to the uninterrupted hyperopic defocus condition.…”
Section: Discussionsupporting
confidence: 94%
“…In human eyes, however, the findings have been mixed. Whilst most studies have reported comparable magnitudes of change in choroidal thickness and/or axial length in response to myopic and hyperopic defocus, 12–16 a recent investigation found a greater response to hyperopic than to myopic defocus 17 . The reasons underlying these differences in the magnitude of response to defocus are not obvious, but could be related to the refractive error of the cohort tested 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After a few months of rapid axial length elongation, which occur in the first 3 to 6 months after birth, growth slows down for the next two years, and by the time a three-year-old is born, he or she has reached adult size (11) .…”
Section: Age Variationmentioning
confidence: 99%